Marriage Reverse Annuity Contract and Reverse Mortgage – Application of a Generalized Model of Reversionary Annuity - Marciniuk, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of the paper is applying the generalized model of reversionary annuity to determine the benefit of marriage reverse annuity contracts and reverse mortgages. First of all, benefits depend on the age of spouses, their future lifetime and the real value of their properties which, in turn, determines the place where they live. In addition, the frequency of payments affects the amount of benefit. Therefore, the periodic benefits are determined for some regions of Poland on the basis of real Polish data from 2015, which mostly comes from The Central Statistical Office of Poland. Calculations of annuities are based on the fixed interest rate and the interest rate function depending on time t for Polish real data. The results are later compared
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 297-306
Keywords: reverse annuity contract; reverse mortgage; reversionary annuity